2021
DOI: 10.1038/s41598-021-90254-y
|View full text |Cite
|
Sign up to set email alerts
|

A validated model for predicting live birth after embryo transfer

Abstract: Accurately predicting the probability of live birth and multiple gestations is important for determining a safe number of embryos to transfer after in vitro fertilization. We developed a model that can be fit to individual clinic data for predicting singleton, twin, and total live birth rates after human embryo transfer. The predicted and observed rates of singleton and twin deliveries were compared in a tenfold cross-validation study using data from a single clinic. The model presented accounts for patient ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Particularly, Abdullah et al observed that patients with POR with younger age and low prognosis (POSEIDON 3) showed an acceptable probability of live births and better perinatal outcomes compared to their older counterparts (POSEIDON 2), emphasizing the influence of age on ART prognosis and increasing the chances of conception with multiple ART cycles with proven evidence 17 . Moreover, according to the mathematically-validated model for predicting live birth rate after embryo transfer developed by Awadalla et al, age and embryo morphology take crucial component in deciding ART outcome 18 , 19 . The discrepancy of results between this and previous studies could have been due to the relatively lower AMH level in our patients, as the clinical nature of the current study was at a tertiary hospital specializing in treating older infertile patients with severely diminished ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Abdullah et al observed that patients with POR with younger age and low prognosis (POSEIDON 3) showed an acceptable probability of live births and better perinatal outcomes compared to their older counterparts (POSEIDON 2), emphasizing the influence of age on ART prognosis and increasing the chances of conception with multiple ART cycles with proven evidence 17 . Moreover, according to the mathematically-validated model for predicting live birth rate after embryo transfer developed by Awadalla et al, age and embryo morphology take crucial component in deciding ART outcome 18 , 19 . The discrepancy of results between this and previous studies could have been due to the relatively lower AMH level in our patients, as the clinical nature of the current study was at a tertiary hospital specializing in treating older infertile patients with severely diminished ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Considering only multiple-embryo transfers, the best-fit UNI using previously described methods ( 16 ) was 0.52 for fresh day 3 embryo transfers, 0.48 for frozen day 3 transfers, 0.60 for fresh day 5 transfers, and 0.66 for frozen day 5 transfers. A UNI of 0.66 represents favorable factors for embryo implantation 66% of the time.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described a model for predicting the risk of multiple gestations after transfer of multiple embryos ( 9 , 10 , 16 ). This model allows for inclusion of quantitative measures of uterine receptivity and embryo competence.…”
Section: Methodsmentioning
confidence: 99%
“…It would not be reasonable to expect guarantees of live births even on the basis of equal opportunities to access ART. In fact, the rate of live births using IVF can vary widely, depending on age group and other factors (Awadalla et al 2021), despite individual clinics advertising high rates of success (Timoney 2022). According to the Human Fertilisation and Embryology Authority (HFEA n.d.) in the United Kingdom, around three-quarters of IVF treatment is unsuccessful-meaning many hopeful parents may unfortunately not conceive at all, even with assistance.…”
Section: A Duty-based Accountmentioning
confidence: 99%